Marketing Communications Plan. Case: Lapin Retriittisafarit - Moilanen, Susanna (Rovaniemen ammattikorkeakoulu, 2012)
The objective of this thesis was to find out the best marketing communications channels and tools for a new tourism company in Rovaniemi. The subject derived from the personal interest to marketing and its communications tools and channels. As the company is new, it did not have a functioning marketing plan yet. The outcome was to create a cost-effective marketing communications plan which the company was able to decide to what extend to implement it. The goal was to get visibility for the company and increase its sales and profit. The company wanted to concentrate on international individual travellers so a quantitative research was made to foreign tourists in the Arctic Circle. The survey was planned together with the commissioner and implemented during three days in the spring 2012. The results were analysed and the suggestions for the marketing strategies were proposed based on the responds. Three marketing books were mainly used as a basis for the theory part. Also scientific articles and Internet sources were used to find reliable information. The research revealed that Internet has a strong influence on people’s buying behaviour. That is why it was suggested for the company to invest most on e-communications. As there are many different marketing communications tools and channels, it was suggested for the company to choose the most effective ones based on the survey and use them as an integrated way. Opinnäytetyön tavoitteena oli selvittää tehokkaimmat markkinointiviestintäkanavat uudelle matkailualan yritykselle Rovaniemellä. Aihe muotoutui omasta kiinnostuksesta markkinointiin ja sen eri viestintäkeinoihin sekä yrityksen puutteelliseen markkinointistrategiaan. Yrityksellä ei ollut vielä käytössä markkinointisuunnitelmaa, joten päämääränä oli kehittää sellainen. Suunnitelman tuloksena yritys saisi näkyvyyttä markkinoilla ja kasvattaisi myyntiä sekä tuloja. Yrityksen pääkohderyhmänä olivat ulkomaalaiset yksityiset matkailijat. Heille kohdistettu kvantitatiivinen kysely toteutettiin Napapiirillä keväällä ...